ANALISIS KEBERLANJUTAN USAHA UMKM DI PROPINSI BANTEN - Yudi Nur Supriadi (JMB : Jurnal Manajemen dan Bisnis, 2018)
This study aims to analyze the variables of strategy implementation ofgeneric learning strategies to the sustainability variables of SMEsbusiness, this study provides a good understanding of theoretical andmanagerial steps that are not done by entrepreneurs of SMEs. Thesuccess of the business will be ensured to survive in the midst ofindustrial processing and weakening the economy both regionally andglobally. Example of study 170 SMEs using SME cluster system in theprocessing industry in Banten Province. Data processing techniques usingquestionnaires. To test the predefined relationship model, the researcheruses a 23.00 analysis tool that can be used together (AMOS). Thevariables generated from the generic strategies of competitive strategiesagainst the significant variables of MSME sustainability and have apositive effect on the sustainability of SMEs business. This research cangive meaning for the sustainability of UMKM business in order to survivein global competition with big industry today and future